Functional and Structural Evaluation of Sildenafil in a Rat Model of Acute Retinal Ischemia/Reperfusion Injury - Ezra-Elia, Raaya; Silva, Germana Alegro da [UNESP]; Zanoni, Diogo Sousa [UNESP]; Laufer-Amorim, Renee [UNESP]; Couto do Amaral, Andreia Vitor; Laus, Jose Luiz [UNESP]; Ofri, Ron (Taylor & Francis Inc, 2017)
Purpose: Retinal ischemia is a common cause of visual impairment and blindness. Sildenafil, a PDE5 inhibitor which inhibits cGMP degradation and in turn prolongs the effect of nitric oxide, has been shown to be protective in a number of ischemia/reperfusion (I/R) injuries, as well as in neuronal damage. We hypothesized that treatment with sildenafil might be neuroprotective in a model of acute retinal I/R injury.Methods: Anterior chamber cannulation was performed to induce unilateral I/R injury in 38 Lewis rats. Animals received intraperitoneal injections of sildenafil (0.5 and 1 mg/kg once a day, for a period of 7 and 18 days, respectively), or saline. Electroretinography recordings, retinal ganglion cell (RGC) counts following retrograde labeling with fluorogold, histopathology, and immunohistochemistry (IHC) using antibodies against PDE5, NOS2, caspase-3, caspase-9, and Bcl-2 were conducted.Results: No significant differences in electroretinography, RGC counts, or retinal morphometry were observed between experimental eyes of sildenafil- and saline-treated animals. A tendency toward less necrosis in histopathology, and a slight trend toward lower PDE5, NOS2, and caspase-9 and higher Bcl-2 IHC scores were evident in experimental retinas of sildenafil-treated animals.Conclusions: Electroretinography, RGC counts, and retinal morphometry failed to show any neuroprotective effect of sildenafil in acute retinal I/R injury in rats. A slight positive effect of sildenafil was qualitatively indicated by histopathology and IHC.
Keywords: Electroretinography; ERG; IOP; I; R; retinal ganglion cells